2021
DOI: 10.2196/24423
|View full text |Cite
|
Sign up to set email alerts
|

Presence of Urinary Exosomes for Liquid Biopsy of Clear Cell Renal Cell Carcinoma: Protocol for a Pilot Feasibility Study

Abstract: Background Approximately 70%-80% of kidney cancers are clear cell renal cell carcinomas (CCRCCs). Patient management is based on imaging (abdominal ultrasound and computerized tomography), surgical excision of the tumor, and pathological analysis. A tissue biopsy is therefore necessary to confirm the diagnosis and avoid unnecessary nephrectomy. For metastatic cancers, a tissue biopsy is essential for establishing the targeted therapy. This biopsy of tumor material is invasive and painful. Other tec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…found five novel mRNAs specific for stage I ccRCC in urinary exosomes, namely NME2, AAMP, CAPNS1, VAMP8, and MYL12B ( 70 ). In addition, a pilot study on the development of a reliable technique to detect exosomal CA9 in the urine of CCRCC patients for molecular diagnosis of CCRCC is underway in France ( 71 ).…”
Section: Exosomes Offer Potential Targets For Early Diagnosis Of Ccrccmentioning
confidence: 99%
“…found five novel mRNAs specific for stage I ccRCC in urinary exosomes, namely NME2, AAMP, CAPNS1, VAMP8, and MYL12B ( 70 ). In addition, a pilot study on the development of a reliable technique to detect exosomal CA9 in the urine of CCRCC patients for molecular diagnosis of CCRCC is underway in France ( 71 ).…”
Section: Exosomes Offer Potential Targets For Early Diagnosis Of Ccrccmentioning
confidence: 99%
“…Oncosomes, which are present in body fluids at high concentrations [ 114 ], have been described extensively as structures of prognostic and diagnostic value [ 14 , 34 ]. They can be extracted and analyzed regarding their embedded nucleic acids and proteins by performing liquid biopsies which have previously been used as a less invasive tool for the detection of biomarkers like circulating tumor cells (CTCs) [ 56 ].…”
Section: Pathophysiology In Different Urological and Nephrological Or...mentioning
confidence: 99%
“…Recently, some independent studies demonstrated that specific exo-miR might serve as promising agents for the diagnosis and monitoring of RCC [ 56 , 100 , 108 ] (NCT04053855). Wang et al and Zhang et al found that the expression of serum-derived circulating exo-miR-210 in patients with ccRCC was significantly elevated which was associated with metastasis and poor prognosis, and in turn levels significantly decreased within the first week after surgical tumor resection.…”
Section: Pathophysiology In Different Urological and Nephrological Or...mentioning
confidence: 99%
See 1 more Smart Citation
“…Some commercial kits for isolation of urinary exosomes have been available. Besides the new markers such as cirRNAs, the markers already found in tumor tissues are also possible paths to be explored in liquid biopsy in future (22). The isolation method of urinary exosomes suitable for clinical laboratory use remains the main challenge.…”
mentioning
confidence: 99%